Literature as National Institution : Studies in the Politics of Modern Greek Criticism - Lambropoulos, Vassilis (Book collections on Project MUSE., 2014)
This book examines how the practices of criticism establish a particular domain of knowledge, the truth of literature. As a discussion of the ideology and politics of literary knowledge, it concentrates on constitutive elements of its production: the intertextuality of writing, the mediatedness of understanding, the formative role of reading expectations, the enabling presence of relevant literacy, the conditioning horizon of expectations, and the economic character of axiology. The main argument advanced is that criticism, by constructing literature as an ethnic heritage and communal treas.